EVALUASI MUTU FISIK SEDIAAN KRIM PILIS TRADISIONAL INDONESIA (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2020)
Maternal care after childbirth in Indonesia has increased, one of which is the use of pilis. Pilis is a traditional medicine that is applied to the forehead by pounding and dissolving with water. Pilis consist of turmeric, galangal, fennel, cinnamon, nutmeg, betel. Pilis can be formulated in cream. The purpose of this study was to determine the results of physical tests of Indonesian traditional pilis cream. This study used a descriptive research method that describes the results of physical tests of creams including organoleptic test, homogeneity test, pH test, spreadability test, and sticky power test. The results showed the Indonesian traditional pilis cream, it had a yellowish-brown color, a distinctive smell of pilis and a half solid form. The cream was homogeneity, pH cream is 7.7. Spreadability cream without load 3.63cm, with a load of 50 grams 3.80 cm, with a load of 100 grams 4.00 cm, with a load of 150 grams 4.23 cm, with a 1.11 seconds sticky power. Conclusion is organoleptic test, homogeneity test, and pH test according to the standard while the spread and adhesion test was not according to the standard.